Clinicopathological characteristics of serrated polyps as precursors to colorectal cancer: Current status and management. Issue 2 (February 2017) - Okamoto, Koichi; Kitamura, Shinji; Kimura, Tetsuo; Nakagawa, Tadahiko; Sogabe, Masahiro; Miyamoto, Hiroshi; Muguruma, Naoki; Takayama, Tetsuji
Abstract: Serrated polyps have long been thought to lack malignant potential in the human colorectum. However, identification of the serrated pathway to colorectal cancer based on molecular biology has improved our understanding of the pathogenesis of colorectal cancers. Accordingly, serrated polyps such as traditional serrated adenoma and sessile serrated adenoma/polyps (SSA/P) are now considered to be precursor lesions of the serrated pathway. Recently, serrated polyps were classified into three subtypes, consisting of hyperplastic polyp, SSA/P, and traditional serrated adenoma, according to the World Health Organization classification. It has been suggested that SSA/P in the proximal colon are a precursor lesion of pathogenesis of colorectal cancer and are characterized by BRAF mutation and a CpG island methylator phenotype with or without microsatellite instability. However, SSA/P is more challenging to detect by colonoscopy and is likely to account for some interval cancers, particularly in the proximal colon because it presents flat or sessile, isochroous appearance, and occasionally has a mucous cap. Furthermore, the possibility has been raised that pathologists misclassify SSA/P as hyperplastic polyp. It is important for gastroenterologists to recognize the endoscopic features of serrated polyps to facilitate their detection and removal and also to establish postpolypectomy surveillance guidelines. In this review, we discuss the recent classification of serrated polyps; the molecular characteristics of the serrated pathway; appropriate diagnostic methods using endoscopy, including a new image‐enhanced endoscopic technique; and management of these lesions.